Death by violence in The Huallaga, a possible effect of the structural determinants of health inequities - Oyola García, Alfredo Enrique (2016)
Mr. Editor. In the review article written by Garmendia (1) on violence in Peru, he has very well pointed out the VRAEM as an example of the violence that exists in our territory, since at least three departments - of the five that make up this valley - are among the five areas with the highest mortality from violence in our country and with a higher risk of death from this cause than the rest of the Peruvian population (2).